Amamentação: capacitando os profissionais de enfermagem - Benites, Marília Deltreggia (2013)
Breastfeeding needs to be taught, because the lack of knowledge about breastfeeding by mothers has been determinant of early weaning. Capabilities in the area of promotion of breastfeeding are key to a good practice, especially nursing professionals serving mothers in maternity wards. In this scenario, the problem-based education presents itself as a powerful tool in supporting breastfeeding and the transformation of everyday practices. This study aimed to develop a training program on breastfeeding with nursing professionals serving mothers and infants in the hospital from the perceptions, knowledge and practices on breastfeeding these professionals and their training needs. It is interventional study of qualitative and quantitative approach carried out with 42 nurses (22 auxiliaries, 13 technical and 7 nurses) who answered a questionnaire addressing concepts, knowledge and practices on breastfeeding. The content relating to perceptions about breastfeeding and practices of health professionals in breastfeeding support were organized according to Discurso do Sujeito Coletivo (Collective Subject Discourse) and analyzed in the form of thematic analysis. We used a simple frequency analysis on issues related to knowledge and practices on breastfeeding. The results supported the implementation of an educational program focused on the identified needs. It was found that the profile of the majority of the collaborators is young adult (76.2%), mothers who breastfed their children, but only 57% participated in training on breastfeeding. With respect to educational practices, most of them guide mothers about breastfeeding and its advantages and care about skin cracks, besides questioning about the difficulties in breastfeeding. However, only 69% check a feeding most of the time. Collective discourses emerged three themes representing the meaning of breastfeeding: ideal food, mother-child bond, and health and wellness, showing the traditional and technical conception of breastfeeding related to the advantages that it brings to the child. These collaborators feel the need to be trained to support mothers in breastfeeding, pointing to the realization of the educational program. There was a need to discuss and deepen the themes: observation of breastfeeding techniques, difficulties experienced by mothers, care about mammary engorgement, poor milk letdown, exclusive breastfeeding and the Ten Steps to Successful Breastfeeding. For this purpose, three meetings have been developed in which the strategy adopted was Teams Based Learning (TBL), which is based on the interaction of small groups and ensures the application of the concepts studied in solving real problems. It is believed that training with active methodology (TBL) guided by the learning needs had positive results, as the professionals who participated 10 have shown great interest in learning the correct way and help mothers in breastfeeding support, feeling compromised to multiply the contents discussed with other professionals. The contribution of this study was mainly due to the impact of educational action and the use, unprecedented in our country, of a TBL training on breastfeeding for nursing professionals. It is important that these professionals have access to courses and training to keep up and improve their daily practices